Censorship detected in BY (Belarus) - Voidly (2026)
CRITICAL severity censorship detected in Belarus. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: BY-2026-1465
Keywords: censorship; BY; censorship; critical